Maritime surveillance with synthetic aperture radar - Di Martino, Gerardo; Iodice, Antonio (Radar, sonar and navigation,, 2020)
This book covers the use of SAR for maritime surveillance applications. It provides a comprehensive source of material on the subject, divided into two parts. The first part deals with models and techniques, while the second part is devoted to maritime surveillance applications. Each chapter covers the basic principles, a critical review of the current technology, techniques and applications, and the latest developments in the field.